A Stable Agrobacterium rhizogenes-Mediated Transformation of Cotton (Gossypium hirsutum L.) and Plant Regeneration From Transformed Hairy Root via Embryogenesis - Cui, Min-Long; Liu, Chen; Piao, Chun-Lan; Liu, Chuan-Liang (Frontiers in Plant Science, 2020)
Genetic transformation is a powerful tool to study gene function, secondary metabolism pathways and molecular breeding in crops. Cotton (Gossypium hirsutum L.) is one of the most important economic crops in the world. Current cotton transformation methods take at least seven to culture and are labor-intensive and limited to some cultivars. In this study, we first time achieved plantlet regeneration of cotton via embryogenesis from transformed hairy roots. We inoculated the cotyledon explants of a commercial cultivar Zhongmian-24 with A. rhizogenes strain AR1193, harboring a binary vector pBI121-GFP that contained the NPT II (neomycin phosphotransferase) gene and the GFP (green fluorescent protein) gene as a fluorescent marker in the T-DNA region. 82.6% explants produced adventitious roots, of which 53% showed GFP expression after transformation. 82% of transformed hairy roots produced embryonic calli, 12% of which regenerated into stable transformed cotton plants after 7 months of culture. the integration of GFP in the transformed cotton genomes were confirmed by PCR (Polymerase chain reaction) and Southern blot analysis as well as the stable expression of GFP were also detected by semi-quantitative RT-PCR analysis. The resultant transformed plantlets were phenotypically, thus avoiding Ri syndrome. Here we report a stable and reproducible method for A. rhizogenes-mediated transformation of cotton using cotyledon as explants, which provides a useful and reliable platform for gene function analysis of cotton.